In Silico Analysis Prediction of B-Cell Epitope as a Vaccine Candidate for SARS-CoV-2 B.1.617.2 (Delta) Variant - Mauritz Nicolaas Wattimena; Wijanarka Wijanarka (Faculty of Medicine, Universitas Diponegoro, 2022)
Background: The COVID-19 pandemic by SARS-CoV-2 has caused many losses. One way to prevent the spread of this virus is to get vaccinated. However, the latest SARS-CoV-2 variants, including variant B.1.617.2 (Delta) are doubtful to be inhibited by existing vaccines because of mutations. Therefore, we need a new vaccine candidate that is effective against this SARS-CoV-2 variant. Through an immunoinformatics approach with various software and analysis websites, vaccine candidates can be predicted in a short time.Objective: Identity, analyze, obtain, and confirm the selected B-cell epitope sequence that can be used as a vaccine candidate for the SARS-CoV-2 B.1.617.2 (Delta) variant.Methods: This research was conducted by isolating the amino acid peptide sequence in the SARS-CoV-2 B.1.617.2 (Delta) variant protein spike from the Protein Data Bank which is suspected to be an immunogenic epitope and can be used as a vaccine candidate. A Series of tests were carried out such as antigenicity, toxicity, allergenicity, and BLAST® protein to ensure that this vaccine candidate is safe for later application into the human body. The next stage is a conservation analysis to see its potential by comparing it with the SARS-CoV-2 Delta (B.1.617.2) variant spike protein sequence in Indonesia. The study ended by mapping amino acid peptides to the SARS-CoV-2 Delta (B.1.617.2) variant spike protein using the Biovia Discovery Studio Visualizer v21.1.0.20298 2020 software to ensure that the selected sequences were epitope.Results: From the five amino acid peptides that have been isolated, the FTNVYADSFVIRGDEVRQIAPGQTGKIADYNYKLPDDFT epitope sequence has good results than the others. It is probable an antigen, non-toxic, non-allergen, and non-homolog to the human body protein.Conclusion: Based on this in silico study, it was found that the FTNVYADSFVIRGDEVRQIAPGQTGKIADYNYKLPDDFT epitope sequence was the best to be used as a vaccine candidate of SARS-CoV-2 B.1.617.2 (Delta) variant.Keywords: SARS-CoV-2 B.1.617.2 (Delta) variant, B-cell epitope, vaccine, in silico, immunoinformatics.